A DESCRIPTIVE STUDY OF IMMEDIATE CAUSE OF DEATH IN COVID-19 HOSPITAL DEATH REPORTED AT TERTIARY CARE HOSPITAL IN WESTERN MAHARASHTRA. (Journal of Forensic Medicine & Toxicology, 2024)
Background: The Coronavirus Disease 2019 (COVID 19) pandemic has had serious worldwide consequences. Even though the disease can affect any age group, the elderly individuals and patients with comorbidities are at risk for severe disease. AIM: The aim of the study is to study Immediate Cause of Death in Covid-19 Hospital Death reported at Tertiary Care Hospital in Western Maharashtra. Methodology: The patient demographic profile was collected from hospital admission slip. Duration of immediate cause and antecedent cause of death were noted from the Medical certificate of cause of death. Total of 434 COVID 19 death reported during the period.
Keywords: COVID-19; Co-morbidities; Antecedent cause; Immediate cause